Bahasa English - Brilliane Salsa; David Sukardi Kodrat (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study aims to analyze the impact of Social Media Marketing and Influencer Endorsement on Consumer Purchase Decision, with Brand Awareness as a mediating variable, using the Theory of Planned Behavior (TPB) as the theoretical framework. TPB is applied to understand how attitudes, subjective norms, and perceived behavioral control influence consumer intentions and purchase decisions. The data were analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS). The results show that Social Media Marketing and Influencer Endorsement do not have a direct effect on consumer purchase decisions. However, Brand Awareness has a positive and significant impact on purchase decisions. Furthermore, mediation analysis reveals that Social Media Marketing and Influencer Endorsement have a positive and significant effect on consumer purchase decisions through the mediating role of Brand Awareness.